Besouro/ Abejorro/ Beetle/ Maggiolino/ Hanneton/ Käfer / Enema: a contrastive lexical analysis of the term “besouro” and its derivatives - Costa Neto, Eraldo Medeiros; Gouw, Monique Sian (SITIENTIBUS série Ciências Biológicas, 2005)
Beetles are culturally significant insects for human beings due to the great number of described species (more than 300.000) and their considerable variety in size, color, kind, and habits. By considering this fact, the present article deals with the descriptive semantics of the term “beetle”, its synonymic equivalents, and derivative words by recording the lexicographic description showed in dictionaries of different languages. Data were obtained from October to November 2004 and February to March 2005 by means of consulting 47 dictionaries of Italian, German, Spanish, French, English, Portuguese, and Tupi-Guarani. These lexicons are deposited at the Central Library of the Universidade Estadual de Feira de Santana. Data were analyzed through a semasiologycal approach by recording the denotative meaning of the lexeme beetle itself and the metaphors, metonymies, and idiomatic expressions which are associated to this vocable in the Portuguese from Brazil and its equivalent terms in other idioms. Results show that the meanings related to the lexeme beetle are peculiar to each language. The connotative meaning appeared in all lexicons, excluding in German and Tupi-Guarani. It was observed that both the vocables related to the lexeme and the semantic descriptions almost always refer to insects known as scarabs and resembling types (family Scarabaeidae). This suggests that this group of beetles may have been considered as a prototypic group in the process of nominative identification of the hundreds of millions of insects that share the world with human beings.